Ruptured Popliteal Artery Aneurysm - Rossi, Umberto G.; Petrocelli, Francesco; Cariati, Maurizio (AORTA, 2021)
Rupture of a popliteal artery aneurysm is an uncommon event in an uncommon disease. We present the case of an 88-year-old female with a ruptured popliteal artery aneurysm that was diagnosed by multidetector computed tomography and treated by an endovascular approach.
Keywords: popliteal artery; aneurysm; imaging; aging; endovascular